(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article discusses about the role of Islam in human development. The importance and tasks of Islamic values in the development of national morals and manners were analyzed, and it was proposed to apply these values to the upbringing and education process of the young generation.